2021
DOI: 10.1109/tap.2021.3083768
|View full text |Cite
|
Sign up to set email alerts
|

Leaky-Wave Radiation From 2-D Dielectric Lattices Excited by an Embedded Electric Line Source

Abstract: This paper presents an analytical and numerical investigation of the radiation features of an interesting class of electromagnetic bandgap (EBG) structures excited by an electric line source. The radiation from two-dimensional (2-D) lattices made with lossless dielectric cylinders, typically optimized by using the Bloch analysis of the corresponding 2-D photonic crystals, are originally investigated in terms of leaky waves. A thorough modal analysis of open waveguides, composed by a finite number of periodic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Directive radiation by elementary sources embedded in PCLWAs is related to the presence of a band-gap between dielectric and air bands in the corresponding 2-D PC lattices and it is observed at the lower edge of the air band [3]- [5], [15]. Hence a preliminary Bloch-wave analysis of the DRPC and HPC 2-D lattices is needed to fix geometrical and physical parameters of the PCLWA.…”
Section: Gap Maps and Field Plots For A Square Lattice Of Circular Di...mentioning
confidence: 99%
See 3 more Smart Citations
“…Directive radiation by elementary sources embedded in PCLWAs is related to the presence of a band-gap between dielectric and air bands in the corresponding 2-D PC lattices and it is observed at the lower edge of the air band [3]- [5], [15]. Hence a preliminary Bloch-wave analysis of the DRPC and HPC 2-D lattices is needed to fix geometrical and physical parameters of the PCLWA.…”
Section: Gap Maps and Field Plots For A Square Lattice Of Circular Di...mentioning
confidence: 99%
“…2(a), formed by N y = 12 circular voids in the transverse y-direction). Here, adopting the leaky-wave approach proposed in [15] and using the tailored numerical procedure developed in [18], the directive features of such kind of radiators have been investigated. A complete analysis, including structures with lossless dielectric rods in free space as well as the dual configuration consisting of circular voids in a hosting lossless dielectric medium, where both even and odd number of rods or voids are considered, is performed.…”
Section: Modal Field Symmetries and Directive Radiation In Open Waveg...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is identified more clearly in Figure 3b, where the three‐dimensional dispersion diagram of the lattice of Figure 3a is plotted. A mode with k x = π / a and k y = 0 can also propagate at the same frequency, but it has been shown that single modes can be selectively excited in a square lattice [31]. Any lattice mode different from the radiation one will be referred to as spurious or unwanted mode.…”
Section: Analytical Frameworkmentioning
confidence: 99%